The Effect of Tidal Current on the Length of Turning Basin Using Maneuvering Simulation - I Putu Sindhu Asmara; Kharis Abdullah; Alif Nur Rochmad; Syafril Mayu Dinata; Sunardi Sunardi (Department of Naval Architecture - Diponegoro University, 2026)
The development of a new port must consider several factors for efficient investment and effective operation. One of those is the turning basin dimensions, which affects the dredging area. This study aims to determine the length of the turning basin. The container ships shall turn before berthing to make them easier to tow out of the jetty in an emergency. A berthing maneuver simulation was performed under extreme conditions of 20 knots wind speed and 5 current speed variations, from 0.75 to 1.75 knots, using the Mathematical Maneuvering Group model. Environmental disturbances cause the approaching vessel to drift when tugboats push it to the jetty. The criteria used for the success of the berthing maneuver are the safe interaction distance (less than 30 m) and the acceptable berthing speed (less than 0.15 m/s). According to a standard the diameter of turning basin is 2L. Based on maneuvering simulation results, the length of the turning basin varies linearly with the current velocity.